2022
DOI: 10.1007/s10113-022-01878-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of endangered bird species to land-use changes in an agricultural landscape in Germany

Abstract: Land-use intensification in agroecosystems has led to population declines in many taxonomic groups, especially farmland birds. Two contrasting conservation strategies have therefore been proposed: land sharing (the integration of biodiversity conservation in low-intensity agriculture) and land sparing (the spatial separation of high-yielding agriculture and areas for conservation). Despite the large academic interest in this field, only few studies have taken into account stakeholders’ perspectives of these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 51 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…In particular the transition from extensive to intermediate grassland use results in a strong biodiversity loss also on larger spatial scales as it leads to a homogenization of grassland communities (Gossner et al, 2016). Closely related are negative effects on bird and insect species richness which were discovered for intensively used grasslands (Chisté et al, 2016;Jungandreas et al, 2022). In addition, studies found a reduction of soil carbon through intensive grassland use (Ward et al, 2016;Kühnel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular the transition from extensive to intermediate grassland use results in a strong biodiversity loss also on larger spatial scales as it leads to a homogenization of grassland communities (Gossner et al, 2016). Closely related are negative effects on bird and insect species richness which were discovered for intensively used grasslands (Chisté et al, 2016;Jungandreas et al, 2022). In addition, studies found a reduction of soil carbon through intensive grassland use (Ward et al, 2016;Kühnel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%